Estimating the associations between women’s maltreatment in childhood and inflammatory biomarker levels prior to and during pregnancy - Bohao Wu; Chirag M. Vyas; Adrián A. Medina; Natalie Slopen; Shruthi Mahalingaiah; Jorge E. Chavarro; Rajarshi Mukherjee; Marc Weisskopf; Andrea L. Roberts (PLoS ONE, 2025)
Background Maternal childhood maltreatment has been associated with higher risk of adverse neurodevelopment in offspring. Chronic systemic inflammation has been associated with childhood maltreatment and has been identified as a gestational risk factor for adverse neurodevelopment in offspring. Thus, inflammation may be a mechanism by which maternal exposure to maltreatment affects offspring neurodevelopment. To estimate associations between women’s childhood maltreatment and four inflammatory biomarkers, C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-alpha receptor 2 (TNF-R2), and interferon gamma (IFN-γ), among women prior to or during pregnancy. Methods A sub-study of the Nurses’ Health Study 3, a prospective cohort, included 329 women, 204 who were contemplating pregnancy and 124 who were pregnant. Approximately 90% of participants were non-Hispanic White and over 60% had a Master’s degree or higher. Maltreatment was assessed using the validated 28-item Childhood Trauma Questionnaire. Associations were calculated using generalized estimating equations. Results Fifty participants (15.2%) were not exposed abuse (n = 28 contemplating pregnancy; n = 22 pregnant) and 81 participants (24.6%) were exposed to moderate or severe abuse (n = 55 contemplating pregnancy; n = 26 pregnant). Childhood maltreatment was not associated with the four inflammatory biomarkers either among participants contemplating pregnancy or among pregnant participants. Conclusions No statistically significant associations were identified between childhood maltreatment and selected inflammatory biomarkers in this sample of well-educated, primarily non-Hispanic White women. These findings should be interpreted with caution given the limited statistical power and measurement variability. Further investigation of these associations in more vulnerable populations might enhance our understanding of biological mechanisms linking maternal childhood abuse to adverse neurodevelopment in offspring.